Knowledge Test for Extension Personnel on National Food Security Mission (Indian Journal of Extension Education, 2022)
National Food Security Mission is one of the pertinent programmes of Indian Government. Developing a knowledge test to measure knowledge level of Extension Personnel on National Food Security Mission was required to study the programme in details. The locale of the study was Uttar Pradesh and Karnataka, hence the knowledge test items were selected keeping the locale under consideration. A Knowledge test comprising 33 items was subjected to relevancy test sought from extension specialists eventually selecting 29 items for the test. The 29 items were pretested on 30 extension personnel from other than the study area. Based on the scores obtained from the pretesting, item analysis eliciting difficulty index, discrimation index and point biserial correlation were done. The items with difficulty index ranging from 0.2 to 0.8, discrimination index above 0.1 and point biserial correlation significant at 5 per cent level of significance were selected. The reliability of the test was measured by using split half method and found to be 0.8. Eventually 24 items were selected for the final knowledge test for extension personnel on National Food Security Mission. This knowledge test can address the knowledge gap existing among the extension personnel by equipping them with right kind of information on NFSM through trainings.